Sexualizing and pathologizing the Other; Reading Doctor Julius Karel Jacobs’s travel account to Bali in the nineteenth century - Jaelani, Gani A. (UI Scholars Hub, 2024)
Since their arrival in the seventeenth century, through the nature of their calling – from the examination of the sick and efforts to acquire knowledge of local medicines – European physicians in the Netherlands East Indies inevitably encountered the local people and their customs. When contact intensified with more frequent journeys into the hinterland, these physicians produced knowledge of the natural world, the culture, and the customs of the region. However, when reading, the travel account of Doctor Julius Karel Jacobs, a Dutch colonial official physician to Bali in 1881, we are offered another perspective. This article discusses how the colonial authorities attempted to consolidate the territory through the expedient of public health issues, conditioning the colonial body for integration, in this case through a vaccination programme. It also analyses the extent the medical vocabularies were used as a strategy for sexual and pathological differentiation. Lastly, examining this travel account underlines the important role of physicians in the colonial biopolitics project.